A mobile air particle system using an optical sensor for haze measurement - Nurulain, S.; Hafiza, Z.; Siera, R.; Musfirah, M.; Salim, M. R.; Hadi, Manap (IOP Publishing, 2021)
This paper presents a development of a mobile haze measurement system which can measure the amount of particulate matter and display in real time. The current haze measurement system called high volume sampler is difficult to move around due to its big size and the reading is not available in real time. Therefore, an alternative for the haze measurement system need to be developed. It uses an optical sensor as a working principle and Arduino board as a microcontroller. The measurement system is able to measure particulate matter from the smoke generated using a mosquito coil. The reading from the developed haze measurement system is verified using a commercial sensor called Dust Mate.